2005
DOI: 10.1183/09031936.05.00065405
|View full text |Cite
|
Sign up to set email alerts
|

Airway narrowing in porcine bronchi with and without lung parenchyma

Abstract: During bronchoconstriction elastic after-loads arise due to distortion of lung parenchyma by the narrowing airway. In the present study, the functional effect of parenchymal elastic after-load on airway narrowing was determined.Airway narrowing was measured in vivo over a range of transpulmonary pressures and compared with in vitro narrowing measured at corresponding transmural pressures. Bronchi were generation 10 with internal diameters of ,4 mm. In vivo luminal narrowing was measured by videobronchoscopy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 42 publications
2
46
3
Order By: Relevance
“…This is somewhat surprising and contradictory to findings suggesting that parenchymal tethering is an important determinant of airway reactivity [8,9,[134][135][136]200]. Although the reason for the discrepancy is not clear, the mid-sized (10th generation) airways studied by NOBLE et al [289] are more cartilaginous than those of comparable size and generation in humans. In fact, the seventh generation human bronchi were found to be cartilage-free [290], but the pig airways appear not to be stiffer than human bronchi [291,292].…”
Section: Other Modulators Of Asmcontrasting
confidence: 54%
See 4 more Smart Citations
“…This is somewhat surprising and contradictory to findings suggesting that parenchymal tethering is an important determinant of airway reactivity [8,9,[134][135][136]200]. Although the reason for the discrepancy is not clear, the mid-sized (10th generation) airways studied by NOBLE et al [289] are more cartilaginous than those of comparable size and generation in humans. In fact, the seventh generation human bronchi were found to be cartilage-free [290], but the pig airways appear not to be stiffer than human bronchi [291,292].…”
Section: Other Modulators Of Asmcontrasting
confidence: 54%
“…Under conditions following a deep inspiration, if lung hysteresis exceeds airway hysteresis, it is predicted that parenchymal tethering would have a minimal effect on airway calibre. In the study by NOBLE et al [289], pressure-strain curves showed minimal hysteresis in the airways in contrast to the much greater hysteresis in the lung lobe, which is consistent with the reported lack of tethering effect reported. However, in that study, airway narrowing was recorded under pressurecontrolled conditions, over a range of inspiratory lung pressures and therefore without the complicating effects of hysteresis caused by a deep inspiration.…”
Section: Other Modulators Of Asmsupporting
confidence: 52%
See 3 more Smart Citations